The order of communication acts in the online news (the application of the pragmatics' speeches in journalism) - Zakie Asidiky (Jurnal Linguistik Terapan, 2016)
This article investigates the order of communication acts in online news as the applica-tion of Pragmatics on speech analysis in Journalism, This research aims to analyze and describe the communication acts used in a selected news on Jakarta Post and to find out the order of communication acts. In the news ‘Taxi protest turns violent as driv-ers target other drivers’, the writer found 5 (five) communication acts used in the narration. They are to describe, to report, to explain, to refer to and to tell. The speech act which is adopted by the used communication acts in the news narration is Representative. Meanwhile, the order of communication acts in the news is started by To tell and ended by To refer to.